Seedling recruitment of native tree species in active restoration forest - Yingluck Ratanapongsai (2020)
© 2020, Hasanuddin University. All rights reserved. Since 1970’s, large are of deforestation and forest conversion to agriculture in the northern mountains of Thailand grew concern of environmental impact. Forest restoration became an important strategy to rapidly increase forest habitat in a wide-scale in Thailand. The Framework Species (FWS) technique is an active forest restoration that has been developed to restored forest habitat and ecosystem on former-agriculture land in the northern Thailand. After planting 20-30 framework species, the method then relies on incoming native tree species to sustain forest succession. However, there has been little known about the recruitment of native tree species and factors limiting the recruitment in this area. The study compared recruit native tree species in the seedling community of the FWS restoration and nearby seed source to assess how many of those are recruit or absent from the community. The factor of seed-dispersed agents and seed sized was investigated as the possible limited factors of the recruitment and compared among 3 restoration periods (at age 6, 10, and 14 years). The result reveals half of native species were absent from the seedling community across all 3 restoration ages. Seed available was a major limitation for the recruitment of native tree species. Big-seeded species had higher chance to be limited than small-seeded species to recruit in the restoration site (p-value = 0.0249 by the Tukey test). whilst seed-dispersed agents were not limited (p-values = 0.420 by Chi square). The FWS forests efficiently facilitated seedlings of native tree species to recruit at the similar recruitment rates across all 3 ages of restoration. However, the technique was still limited in regard of seed available. Species of less common or rarer might need to be included for the FWS plantation in the future to enhance species diversity and better outcome of the restoration.